The effect of organic and metal oxide interfacial layers on the performance of inverted organic photovoltaics - Savva, Achilleas; Petraki, Foteini; Eleftheriou, Polyvios; Sygellou, Lamprini; Voigt, Monika M.; Giannouli, Myrsini; Kennou, Stella; Nelson, Jenny M.; Bradley, Donal D.C.; Brabec, Christoph J.; Choulis, Stelios A. (My University, 2013)
We study the origin of the improvement of the power conversion effi ciency (PCE) of inverted organic solar cells when an interfacial insulating organic layer of polyoxyethylene tridecyl ether (PTE) is introduced between the indium tin oxide (ITO) bottom electrode and the TiOx interfacial layer. XPS and UPS measurements are used to investigate the energy level alignment at the interfaces within the ITO/TiOx and ITO/PTE/TiOx structures and to identify any effects due to chemical interaction and interfacial dipoles. Scanning electron microscopy studies show that the surface structure of the TiOx layer is affected, when it is coated on top of the PTE layer. Surface contact angle measurements show that the incorporated interfacial layer of PTE is more hydrophilic than ITO and thus PTE modifi ed TiO x becomes more hydrophilic. This, in combination with the surface gaps of the PTE interfacial layer, is likely to lead to changed wetting and hydrolysis properties of TiOx when coated on ITO/PTE than on ITO alone. The different TiOx layer quality is refl ected in improved electron selectivity, leading to enhanced fi ll factor, reduced parasitic resistance effects and higher power conversion effi ciency for inverted solar cells with a PTE interfacial layer between ITO and TiOx.
Keywords: Organic photovoltaics; Interfacial layer